Seroprevalence of brucellosis among the high-risk population in Ujjain district, Madhya Pradesh - Riddhi Pradhan; Anand Bhadkariya; Vidit Khandelawal; Vishal Diwan; Waghe SR; Deepak Saxena; Shah H; Manju Purohit (Asian Journal of Medical Sciences, 2022)
Background: Brucellosis is the most common zoonotic disease caused by Gram-negative coccobacillus belonging to genus Brucella. It is a recognized public health problem in developing countries including India. Aims and Objectives: The aims of these study were to determine the seroprevalance of brucellosis in population having occupation dealing with animals and thus are in close contact of animals. Materials and Methods: The study was conducted in semi-urban areas of central India. Blood samples were collected from personnel working in slaughter houses, meat shops, and veterinarians and their close contact and who are willing to participate in study. A total 102 samples collected randomly from butchers (n=20), veterinarians (n=29), and animal handlers (n=53) and were tested for Brucella abortus and Brucella melitensis by a commercial kit which allows the detection of both complete (IgG and IGM) and incomplete antibodies. Results: A total 102 subjects were included in the study and overall prevalence of brucellosis among high-risk group was found to be 2.9%. One veterinarian doctor was also found positive for both B. melitensis and B. abortus. Highest prevalence of brucellosis was found in veterinarians (6.8%) followed by animal handlers (1.8%), and none of the butcher was tested positive for any of the Brucella antibody. Conclusion: The present study screened all possible known high-risk groups for brucellosis and revealed that veterinarians have high chances of getting the infection. Occupation-related disease like brucellosis needs regular surveillance and integration into control and prevention program at a local and national level.